MicroRNA‐222‐3p participates in the development of oral squamous cell carcinoma by targeting CDKN1B. (1st March 2020) - Yang, Kaicheng; Chen, Yanping; Cui, Zifeng; Chen, He; Yang, Lei; Zhao, Jianguang; Luo, Fengyu; Man, Shasha; Zhao, Jianghui; Jin, Lingyu
Abstract: Objective: The aim of this study was to explore the potential role and regulatory mechanism of microRNA (miR)‐222‐3p in oral squamous cell carcinoma (OSCC). Methods: The expression level and prognostic significance of miR‐222‐3p was detected in OSCC tissues. CCK‐8, transwell, and flow cytometry assays were used to explore the effect of miR‐222‐3p on cell proliferation, migration, invasion, and apoptosis. The influence of miR‐222‐3p on cyclin‐dependent kinase inhibitor 1B (CDKN1B) expression was evaluated by luciferase assays, real‐time polymerase chain reaction, and Western blot. Results: We found that miR‐222‐3p was overexpressed in OSCC tissues, comparing with normal tissues. Kaplan‐Meier curves showed that OSCC patients with high expression of miR‐222‐3p ( P  = .003) showed worse overall survival than those patients with low expression of miR‐222‐3p. Multivariate analysis showed that miR‐222‐3p ( P  = .037) expression was an independent prognostic factor of OSCC patients. miR‐222‐3p promoted cell proliferation, migration and invasion and induced the apoptosis of SCC‐15 and Tca‐83 cells. Furthermore, luciferase reporter assays indicated that CDKN1B is targeted by miR‐222‐3p in OSCC cells. Overexpression of CDKN1B inhibited OSCC cell proliferation, migration, and invasion and promoted cell apoptosis rate. Conclusions: miR‐222‐3p affects OSCC cell proliferation, migration, invasion, and apoptosis through targeting CDKN1B, and may be a potential prognostic biomarker for OSCC patients.